Digital Technology in English Language Teaching and Learning (NTU journal for Administrative and Human Sciences (JAHS), 2022)
Today, using technology is an urgent requirement in the process of both teaching and learning English language. As a result, both teachers and learners need more devices and tools in order to accomplish their goals and develop their skills.              This study gives an overview of the recently developed applications of digital technology used in teaching and learning English language. The researchers try to focus on the online classrooms and the applications widely used at recent years after the sudden attack of corona virus that disables the educational systems in most countries over the world.                  The paper also tries to link the pedagogical system based on technology with the theories and methods of education, and finding out to which school such system is related to. The study ends with a brief account on the outcomes of using technology in both language teaching and learning on the language skills i.e. listening, reading, writing and speaking.